2006
DOI: 10.1097/01.bot.0000249435.25751.e8
|View full text |Cite
|
Sign up to set email alerts
|

Is Perioperative Blood Transfusion a Risk Factor for Mortality or Infection After Hip Fracture?

Abstract: Our data suggest that transfusion is not associated with a change in mortality or infection rates in the hip-fracture patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
3
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 17 publications
4
47
3
3
Order By: Relevance
“…Our that blood transfusion was associated with a 25% lower risk of death (Table 5, Figure 2 results of no effect of transfusion on short-term (0-30 and 31-180 days) survival in ICU patients are consistent with results of studies in orthopedic patients 10,15,16 and of some studies in cancer patients. 17,18 However, in other studies in surgical cancer patients and in studies of patients undergoing cardiac surgery, the risk of mortality was increased, for at least 1 year, in patients receiving a transfusion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our that blood transfusion was associated with a 25% lower risk of death (Table 5, Figure 2 results of no effect of transfusion on short-term (0-30 and 31-180 days) survival in ICU patients are consistent with results of studies in orthopedic patients 10,15,16 and of some studies in cancer patients. 17,18 However, in other studies in surgical cancer patients and in studies of patients undergoing cardiac surgery, the risk of mortality was increased, for at least 1 year, in patients receiving a transfusion.…”
Section: Discussionsupporting
confidence: 79%
“…In 2 studies 8,9 in cardiac surgical patients, long-term survival was decreased in patients who received perioperative transfusions. However, in a study 10 of patients undergoing surgery for hip fractures, researchers found no association between transfusion and long-term survival. These limited studies may have little applicability to ICU patients, who are often more critically ill than are cardiac surgery or hip surgery patients.…”
mentioning
confidence: 99%
“…This may be because the population receiving a transfusion had a higher prevalence of comorbidities and thus was inherently predisposed to an increased risk of death 39 . Several studies did not find an association between allogenic blood transfusion and short-term mortality in hip-fracture patients [40][41][42] . However, these findings cannot rule out the possible deleterious effects of allogenic blood transfusion on longer-term mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles describe ways to reduce the risk of complications among patients with hip fractures in the inpatient setting once they leave the operating room [6,9,11,13,14,17,18,20,28,31,33,37,43,44]. These studies have focused on the importance of early mobilization, the use of general versus regional anesthesia to reduce pulmonary complications, the use of pharmacologic anticoagulation to prevent thromboembolic events, and the role of multidisciplinary care pathways for treatment of patients with hip fractures.…”
Section: Introductionmentioning
confidence: 99%